Digitalisasi aspirasi rakyat: Rancang Bangun Sistem Informasi Pengaduan Masyarakat Berbasis Web(Studi Kasus : DPRD Kota Palembang) - Marlindawati; Vivi Sahfitri (Jurnal Ilmiah Matrik, 2026)
The advancement of information technology has encouraged government institutions to improve the efficiency and quality of public services, one of which is through the digitalization of public complaint systems. The Regional House of Representatives (DPRD) of Palembang City, particularly Commission I, does not yet have a web-based complaint system, so the complaint management process is still carried out manually and is prone to delays in handling and potential data loss. This research aims to design and develop a web-based public complaint information system that facilitates citizens in submitting reports online and assists the DPRD in following up on reports quickly and systematically. The system was developed using the Waterfall model, consisting of analysis, design, coding, testing, implementation, and maintenance stages, with PHP as the programming language and MySQL as the database. The results show that the developed system can improve the speed of reporting, the accuracy of data storage, and transparency in complaint handling, which is expected to enhance accountability and public service quality at the DPRD of Palembang City